2009
DOI: 10.2214/ajr.08.1788
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 99mTc-DMSA Dual-Head SPECT Versus High-Resolution Parallel-Hole Planar Imaging for the Detection of Renal Cortical Defects

Abstract: (99m)Tc-DMSA renal cortical imaging using dual-head SPECT offers no statistically significant diagnostic advantage over planar imaging for detection of cortical defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Of the various methods available for doing DMSA renal scans, we used planar images instead of SPECT because the latter would have posed substantial problems in standardization, quality control, and the review process (10). Furthermore, some studies have reported that the SPECT images offer no statistically significant diagnostic advantage over planar imaging for detection of cortical defects (30,34).…”
Section: Discussionmentioning
confidence: 99%
“…Of the various methods available for doing DMSA renal scans, we used planar images instead of SPECT because the latter would have posed substantial problems in standardization, quality control, and the review process (10). Furthermore, some studies have reported that the SPECT images offer no statistically significant diagnostic advantage over planar imaging for detection of cortical defects (30,34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a 99m Tc-DMSA renal cortical SPECT imaging study by dual head gamma camera, reconstruction was performed similarly on both cameras using a Hann prefilter (cutoff frequency, 0.9 cm −1 ; order, 0) and a Butterworth postfilter (cutoff frequency, 0.5 cm −1 ; order, 10) with two iterations and 10 subsets for the detection of renal parenchyma focal defects [29]. …”
Section: Type Of Filters Depending On Type Of Studymentioning
confidence: 99%
“…[ 7 ] Different acquisition methodologies have been used, including planar parallel-hole collimator imaging, planar high-resolution parallel-hole collimator imaging, pinhole collimator imaging, SPECT and PSPECT. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Different acquisition methodologies have been used, including planar parallel-hole collimator imaging, pinhole collimator imaging, single photon emission computerized tomography (SPECT) and pinhole SPECT (PSPECT). [ 4 5 ] Controversy exists regarding the superiority of Tc-99m DMSA SPECT over planner imaging. The purpose of the current study was to compare planar parallel-hole cortical scintigraphy and dual-head SPECT for detection of cortical defects.…”
Section: Introductionmentioning
confidence: 99%